2020
DOI: 10.1007/s10750-020-04349-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic stress parameters of a cased caddis larva (Drusus biguttatus) using spatio-temporally filtered velocity measurements

Abstract: By studying hydraulic stress parameters of larvae of the cased caddisfly Drusus biguttatus (Pictet, 1834) in a tributary of the Schwarze Sulm (Carinthia, Austria), we aimed on (1) detecting the flow properties of the spatio-temporally filtered velocity measurements taken, and (2) on defining the hydraulic niche of this caddisfly larva. For this, we took 31 measurement series lasting 30 to 300 s, yielding 2176 single velocity measurements. The probability density functions of the 31 data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In this context, the present estimations showed that fully everted KO notably increased the body surface of the young octopus by a mean of 2/3 of the skin surface in comparison with skin areas with retracted KO. This modular body surface extension and accompanying rough texture probably influence flow forces (such as those of drag and propulsion) on the young octopus during specific times or stages of paralarval life, enhancing or restricting passive transport within oceanic currents and saving energy in a similar way as observed in other invertebrate larvae (Emlet, 1991;Ditsche and Summers, 2014;Waringer et al, 2020). Planktonic octopus hatchlings are quite similar to squid hatchlings in size and locomotion mode, both have a rounded mantle of a few mm in length and relatively large funnel apertures to use constantly during jet propulsion in the water column (Villanueva et al, 1997(Villanueva et al, , 2016Dan et al, 2020).…”
Section: Possible Ko Functions and An Evolutionary Perspectivementioning
confidence: 93%
“…In this context, the present estimations showed that fully everted KO notably increased the body surface of the young octopus by a mean of 2/3 of the skin surface in comparison with skin areas with retracted KO. This modular body surface extension and accompanying rough texture probably influence flow forces (such as those of drag and propulsion) on the young octopus during specific times or stages of paralarval life, enhancing or restricting passive transport within oceanic currents and saving energy in a similar way as observed in other invertebrate larvae (Emlet, 1991;Ditsche and Summers, 2014;Waringer et al, 2020). Planktonic octopus hatchlings are quite similar to squid hatchlings in size and locomotion mode, both have a rounded mantle of a few mm in length and relatively large funnel apertures to use constantly during jet propulsion in the water column (Villanueva et al, 1997(Villanueva et al, , 2016Dan et al, 2020).…”
Section: Possible Ko Functions and An Evolutionary Perspectivementioning
confidence: 93%
“…In total, 101 data sets were taken for fifth instar larvae. The flow to which larvae are (8) U (gSy) * 0.5 = 2.5ln Rey k + 5.3 − 0.1206(Re − 5) exposed in their natural setting is highly fluctuating (usually turbulent; Waringer et al, 2020) and even the mean velocity profiles (as functions of the distance from the ground) may vary. Furthermore, these flow details are very difficult to measure under field conditions.…”
Section: Field Measurementsmentioning
confidence: 99%
“…In lotic habitats, a tubular case constructed of mineral particles is the most abundant type (Waringer & Graf, 2011). Even so, tubular cases are very different in length, width, weight, curvature, and roughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of taxa in rivers depends on the capacity of its organisms to occupy different habitats, which, in turn, depends on their body structure (i.e., nails, gills, suction cups, etc.) or shape (hydrodynamic, cylindrical or flattened) developed to persist in a particular habitat [60][61][62].…”
Section: Variables Influencing Macroinvertebrate Distribution At the mentioning
confidence: 99%